identity - Grigoryeva, Elena (project baikal, 2014)
The epoch of globalism’s victorious march is coming to the end. Today’s and tomorrow’s architecture should be based on national roots, nature and distinctions. It is declared in the Memorandum of one of the recent International Union of Architects Congresses. In August 2014 the XXV UIA Congress was held in Durban, South Africa. Its details are given in the beginning of our news section (5). The annual Festival Zodchestvo of Eastern Siberia (ZES) was devoted to identity of Siberian cities. It was held in Krasnoyarsk for the first time in its 14-year history. This issue presents the Festival Chronicle, the Catalogue of Winners and the Report from the ZES 2014 Discussion Club (22, 32, 64). The ZES 2014 Discussion Club became a cross-disciplinary platform, where an architect, a psychologist, a historian, a philosopher, an urbanist, an ethnographer and a culturalexpert shared their views on identity of Siberian cities. Every city has its own unique character. We know it, we feel it. Siberian cities differ from other cities of the world and even from other cities of the European part of Russia. They differ from each other, too. Landscape and history, personalities and communities have formed our cities: Novosibirsk, Kemerovo and Novokuznetsk, Krasnoyarsk, Irkutsk, Ulan-Ude and Yekaterinburg, Balkan Belgrade, Shumen and Akrotiri with its many thousands of years of history have become the principal characters of the issue. At the end of the main section there is a touch of new identity in Majorelle colour in the red city of Marrakesh.